Toxicity and survival outcomes in older adults receiving concurrent or sequential chemoradiation for stage III non-small cell lung cancer in Alliance trials (Alliance A151812). Issue 4 (May 2021) - Maggiore, Ronald J.; Zahrieh, David; McMurray, Ryan P.; Feliciano, Josephine L.; Samson, Pamela; Mohindra, Pranshu; Chen, Hongbin; Wong, Melisa L.; Lafky, Jacqueline M.; Jatoi, Aminah; Le-Rademacher, Jennifer G.
Abstract: Introduction: Optimal treatment for older adults with stage III non-small cell lung cancer (NSCLC) remains unclear. Here we hypothesized that sequential chemoradiation therapy (sCRT) is better tolerated than concurrent (cCRT) but confers acceptable efficacy. We evaluated these strategies in older adults utilizing Alliance for Clinical Trials in Oncology data. Materials and methods: Pooled analyses from 6 first-line stage III NSCLC CRT trials (Cancer and Leukemia Group B 8433, 8831, 9130, 30106, 30407, 39801) were used to compare toxicity and survival outcomes with cCRT versus sCRT in patients age ≥ 65 years. Grade 3–5 adverse events (AEs), progression-free and overall survival (PFS; OS) are reported with adjustment for covariates. Results: Four hundred older adults, of whom 106 (26.5%) had received sCRT and 294 (73.5%) had received cCRT, comprised the cohorts. Virtually all had an Eastern Cooperative Oncology Group performance status (ECOG PS) 0–1 (99%). More grade 3–5 AEs were observed at any time-point with cCRT than sCRT (94.2% versus 86.8%; 95% confidence interval for difference in proportions, 1.3%, 15.5%) and this finding remained after adjusting for length of study treatment ( P  = 0.018). Comparable PFS and OS were observed with sCRT versus cCRT (median: 8.0 versus 9.2 months; median: 11.9 versus 13.4 months, respectively) even after adjustment for age, sex, ECOG PS, body mass index, pretreatment weight loss, stage, and cisplatin-based therapy ( P  = 0.604 and P  = 0.906, respectively). Discussion: These data show that sCRT was associated with less toxicity than cCRT with no associated statistically significant decrease in efficacy outcomes and that sCRT merits further study in this population.